EDUKASI PERSONAL HYGIENE SAAT MENSTRUASI DI PANTI ASUHAN PUTRI AISYIYAH PUCANG GADING - Larasaty, Nurina Dyah; Dhaningtyas, Shalihat Afifah; Sucipto, Mega Rahmawati; Adilla, Aulia Rahmawati; Kusuma, Idfi Widya (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The personal hygiene practices of female students during menstruation at the Aisyiyah Pucang Gading Orphanage remain inadequate. Therefore, a community service program focusing on personal hygiene education during menstruation is essential to improve their health. The method employed involved participatory lectures supported by animated video presentations, games, and quizzes. The materials provided covered puberty education, an explanation of menstruation, including practices for maintaining hygiene during menstruation, and proper methods for disposing of sanitary pads.The results of the educational session revealed high enthusiasm and an increase in the students' understanding. Monthly monitoring and evaluation will be conducted to track progress and outcomes. Thus, the implementation of this educational program has successfully achieved its objectives, and further research is recommended to develop methods, outcomes, and knowledge related to this topic.